Richard Rohr and the Paradigm Shift in Trinitarian Theology - Heryán, Ladislav (Communio viatorum, 2023)
This paper describes Rohr’s shift from the traditional Trini-tarian theology to a new concept of God. Rohr sees Christ as the mysterious essence of all things. The Trinity is an expression of the flowing nature of the Divine. Jesus, through his cross, allowed suffer-ing to change him and the world, so that people could break out of the endless cycle of projecting pain elsewhere and be loved by the real-ity that surrounds them. The implications of this shift for spirituality are considered. People can live with constant prayer, meditation and practice of his words in his presence.